Analisis Kualitas Instrumen Kemampuan Pemecahan Masalah Siswa SMA pada Materi Suhu dan Kalor Menggunakan Model Rasch - Silvi Lutfiah Padilah; Lina Aviyanti; Nurdini Nurdini (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Problem-solving ability is an essential competency in physics learning; therefore, a high-quality assessment instrument is required to measure students' abilities accurately. This study aimed to analyze the quality of a physics problem-solving ability instrument on the topic of temperature and heat using the Rasch Model. This research employed a quantitative approach with a descriptive research design involving 54 senior high school students (26 males and 28 females). The instrument consisted of five essay questions comprising 25 scored sub-items based on Heller's problem-solving indicators. Data were analyzed using Ministep version 5.10.3 software by examining item validity, reliability, item discrimination, item difficulty, Differential Item Functioning (DIF), and the Wright Map. The results showed that 21 sub-items met all item fit criteria, while four sub-items met two of the three criteria. The instrument demonstrated good psychometric quality with a Cronbach's Alpha of 0.89, Person Reliability of 0.88, and Item Reliability of 0.96. Item discrimination was generally good, only four sub-items were identified with DIF, and the Wright Map indicated good targeting between students' abilities and item difficulty. Therefore, the instrument is valid, reliable, fair, and suitable for measuring students' problem-solving ability. It can also serve as an alternative assessment tool for teachers and researchers in physics education.